Marketing Lending Strategy on Products BSI. GRIYA HASANAH. (STUDY KASUS.PT. ISLAMIC BANK, TBK. SITUBONDO BASUKI RAHMAT BRANCH) - Haeroni Haeroni; Muhammad Syaiful Suib (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to improve the marketing strategy of BSI Griya Hasanah products. This research is located at PT. Bank Syariah Indonesia Situbondo Basuki Rahmat branch. The research method used is qualitative case studies. Data acquisition uses observation, interview, and interview methods of branch heads, microstaff, and CBS. Data analysis procedures used data selection, data reduction, data presentation and drawing conclusions. The results show that the strategy applied to BSI GriyaHasanah's financing products is focused on; product, price, place, promotion, people, physical evidence, and procces. The results of this study show that. Marketing Strategy Lending improves the marketing of griyahasanah products. Marketing Lending. Strategy is a good contribution to the sustainability of BSI GriyaHasanah Products towards fierce banking competition in the global future.